2011
DOI: 10.1080/02589001.2011.539011
|View full text |Cite
|
Sign up to set email alerts
|

More women in the Tanzanian legislature: Do numbers matter?

Abstract: This study examines the changes that followed the rise in the number of female parliamentarians in the Tanzanian legislature and the contextual factors undermining the potential power of the increased number of female MPs. As found in a number of other countries, with more women in parliament, women's interests, concerns and perspective have been better incorporated into parliamentary debates and policy-making in Tanzania. However, the increase in female parliamentary representation challenges the existence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 21 publications
5
37
1
Order By: Relevance
“…Complementing recent studies of women's legislative representation in Africa (Bauer and Britton 2006;Tripp and Kang 2008;Yoon 2010Yoon , 2011, our study suggests that understanding women's political empowerment requires careful attention to informal barriers. Studies of wellestablished democracies have already shown how informal barriers like internal party politics, media bias, and stereotypes limit women's access to the cabinet (Borrelli 29 Substituting the PREG fractionalization index for the EPR number of groups produces comparable results.…”
Section: Resultsmentioning
confidence: 91%
“…Complementing recent studies of women's legislative representation in Africa (Bauer and Britton 2006;Tripp and Kang 2008;Yoon 2010Yoon , 2011, our study suggests that understanding women's political empowerment requires careful attention to informal barriers. Studies of wellestablished democracies have already shown how informal barriers like internal party politics, media bias, and stereotypes limit women's access to the cabinet (Borrelli 29 Substituting the PREG fractionalization index for the EPR number of groups produces comparable results.…”
Section: Resultsmentioning
confidence: 91%
“…Yoon (2011b, p. 91) notes for Tanzania that the increase in women's representation in parliament and the ‘good performance of some female politicians’ has ‘gradually changed the unfavourable cultural and social attitudes toward women in politics’; she quotes the executive director of the Tanzania Media Women's Association, Ananilea Nkya: ‘Both men and women now know that women are capable of leading and being good politicians, and they are willing to vote for women’. In Botswana where women have historically served only as regents and not as chiefs, women chiefs such as the paramount chief of the Balete Mosadi Seboko have revealed the way in which the presence of women ministers and MPs has convinced Botswana that a woman can also serve successfully as chief 22 .…”
Section: African Women Mps' Symbolic Representationmentioning
confidence: 99%
“…In an early assessment of the impact of more women in parliament in Tanzania, Ruth Meena (2004, p. 83) found that women MPs in the early 2000s advocated laws that addressed women's concerns in several areas, including maternity leave, access to university education, sexual and gender-based violence and land reform. More recently, Yoon (2011b) identified several positive impacts from women's increasing legislative representation including the establishment of a women's caucus that provides parliamentary skills training for women MPs, a significant increase in women MPs' contributions to parliamentary debates, a better articulation of women's interests in parliament, a more interactive parliamentary environment (between women and men) than in the past, several legal changes that benefit women (as noted above), and modest increases in women's cabinet presence. Yoon notes that these advances have been made despite ongoing challenges to women MPs including the weakness of the legislature, the limiting power of party discipline, a lack of skills on the part of women MPs and an overall lack of resources available to Tanzanian MPs.…”
Section: African Women Mps' Substantive Representationmentioning
confidence: 99%
“…The donors who sponsored TAMWA's program on gender violence are invisible and do not appear to have taken any credit at all. Other acts that were amended or introduced in the late 1990s and early 2000s with the active involvement of NNGOs are the Land Act of 1999, the Law of the Child Act, and the revised Law of Marriage Act of 2002 (Kismabu and Lugembe 2012;Mosha 2012;Tripp et al 2009:127, 132;Yoon 2011). …”
Section: Historical Context: Partnerships and Policy Making In The 19mentioning
confidence: 98%